Fibrinolysis in Liver Diseases Study of 109 Cases by means of the Fibrin Plate Method - de Nicola, P; Soardi, F (Thrombosis and Haemostasis, 1958)
In 109 patients with liver diseases, fibrinolysis was studied by means of the fibrin plate method. A general increase of the fibrinolytic activity was observed in all liver diseases. This finding was particularly evident for the liver cirrhosis and by studying the spontaneous fibrinolysis in plain and precipitated serum and in plain and heated plates, as well as the streptokinase activated fibrinolysis in plain serum and plain plates. Liver malignancies usually showed a normal or subnormal behaviour, with the only exception of the streptokinase activated, precipitated serum in plain plates. Significant differences were found between liver cirrhosis and chronic hepatitis. In heated plates, the differences between liver cirrhosis and other liver diseases (chronic and acute hepatitis, hepatomegaly with liver impairment, malignancies) were not very much pronounced, when streptokinase activated serum was used. For diagnostic purposes, the most suitable tests for studying the fibrinolytic activity by means of the fibrin plate method in liver diseases, are represented by the following combinations: a. plain serum and plain plates; b. streptokinase activated serum and plain plates.